Sustainable transport and tourism destinations - Zamparini, Luca (Transport and sustainability, 2021)
Transport allows tourists to move from their origins to their destinations and within destinations. The increase in tourism, and in connected mobility, has raised sustainability issues in terms of ecological protection and the economic efficiency of competing destinations. This book examines the links between transport, tourism, and sustainability by means of a series of large case studies covering several countries. Themes, frameworks and proposed policies are discussed throughout the book. The concluding chapter of the book takes an explicitly comparative approach and highlights the new contributions that emerge from the case study chapters for both scholars and practitioners. The Transport and Sustainability series addresses the important nexus between transport and sustainability. It contains volumes dealing with a wide range of issues relating to transport, its impact in economic, social and environmental spheres, and its interaction with other policy sectors. Editors and authors take a wide range of approaches - some volumes are general and some specific in nature, and analyses are advanced from a host of different disciplinary backgrounds and perspectives - but the defining feature is that each contribution is grounded in a firm appreciation of how its contents relate to the broader imperatives associated with transport and sustainability.